Productivity change and fleet restructuring after transition to individual transferable quota management. (December 2015) - Färe, Rolf; Grosskopf, Shawna; Walden, John
Abstract: Productivity change after transition to an individual transferable quota (ITQ) management system is driven by exit of some vessels, entry of other vessels, and changes in productivity of existing vessels. Generally, it is thought that an ITQ system boosts productivity due to the exit of less productive vessels. However, ITQ management systems also create an additional barrier to entry, and more productive vessels may not be able to enter the fishery. This study constructs the Färe–Primont index to measure productivity change for the Mid-Atlantic surf clam and ocean quahog fishery over a 32 year time period, which includes both pre and post-ITQ time periods. The index is then combined with a biomass change index to arrive at a measure of biomass adjusted productivity change. Results show that when biomass changes are considered, positive productivity gains occurred throughout the time period. Further examination of contributions from entering and survivor vessels show that entering vessels had little impact on aggregate productivity, but on an individual basis, they eventually were equal in productivity to survivor vessels. Highlights: A productivity Index showed positive productivity gains post-ITQ. Results differed from prior studies after normalizing results by biomass change. Aggregate productivity change post-ITQ is driven by continuing vessels. Externalities still exist in an ITQ system, which can limit productivity gains.